Decreases in beetle body size linked to climate change and warming temperatures. (30th January 2018) - Tseng, Michelle; Kaur, Katrina M.; Soleimani Pari, Sina; Sarai, Karnjit; Chan, Denessa; Yao, Christine H.; Porto, Paula; Toor, Anmol; Toor, Harpawantaj S.; Fograscher, Katrina
Abstract: Body size is a fundamental ecological trait and is correlated with population dynamics, community structure and function, and ecosystem fluxes. Laboratory data from broad taxonomic groups suggest that a widespread response to a warming world may be an overall decrease in organism body size. However, given the myriad of biotic and abiotic factors that can also influence organism body size in the wild, it is unclear whether results from these laboratory assays hold in nature. Here we use datasets spanning 30 to 100 years to examine whether the body size of wild‐caught beetles has changed over time, whether body size changes are correlated with increased temperatures, and we frame these results using predictions derived from a quantitative review of laboratory responses of 22 beetle species to temperature. We found that 95% of laboratory‐reared beetles decreased in size with increased rearing temperature, with larger‐bodied species shrinking disproportionately more than smaller‐bodied beetles. In addition, the museum datasets revealed that larger‐bodied beetle species have decreased in size over time, that mean beetle body size explains much of the interspecific variation in beetle responses to temperature, and that long‐term beetle size changes are explained by increases in autumn temperature and decreases in spring temperature in this region. Our data demonstrate that the relationship between body size and temperature of wild‐caught beetles matches relatively well with results from laboratory studies, and that variation in this relationship is largely explained by interspecific variation in mean beetle body size. This long‐term beetle dataset is one of the most comprehensive arthropod body size datasets compiled to date, it improves predictions regarding the shrinking of organisms with global climate change, and together with the meta‐analysis data, call for new hypotheses to explain why larger‐bodied organisms may be more sensitive to temperature. Abstract : The study uses long‐term collections of museum specimens to demonstrate that decreases in ground beetle body size over time are linked to increases in autumn temperatures. Field‐collected beetles have decreased in size at a faster rate than predicted by laboratory experiments.